Assessment of Clinicians Knowledge and Perception on Antimicrobial Resistance a Primary Strategy for Antimicrobial Resistance Control (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: antimicrobial resistance; KAP survey; clinicians